Intraoral Digital Impression Technique for a Neonate With Bilateral Cleft Lip and Palate. (September 2019) - Patel, Jilen; Winters, John; Walters, Mark
Objective: Dental casts are an important aspect in the treatment planning, documentation, and analysis of the dental arch forms of infants with cleft lip and palate (CLP). Impression taking in a neonate is a technique-sensitive procedure, which can result in foreign body dislodgement and carries a small risk of aspiration and airway obstruction. The advent of digital dental technologies and intraoral scanning may facilitate safer, more effective, and accurate impressions for CLP infants. Design: A digital intraoral scan of a 3-month-old with bilateral CLP (BCLP) was compared with a conventional alginate impression taken prior to primary lip repair. Setting: Princess Margaret Hospital for Children. Main Outcome Measures: To test the applicability and accuracy of digital impression taking for a neonate with BCLP and palate using digital morphometrics. Results: The average deviation of points ranged above and below the plane of superimposition from +0.78 mm to −0.42 mm with a maximum range of +2.80 mm to −2.80 mm and standard deviation of 0.88 mm. The premaxillary segment showed the greatest degree of variation. Conclusions: This is to our knowledge the first report that illustrates the use of a digital impression system to scan the oral structures of a neonate with BCLP. Digital scanning was found to be fast, accurate, and safe, when compared to a conventional alginate impression technique.